(untitled) (Experimental biology, 2015)
This work considers the dynamic of changes in the species composition of microalgae influenced by external factors on the example of lake Copa in Kokshetau. In result algological of research carried out in 2008-2010 years from microseaweed of lake Copa, 23 kinds are the indicator - saprobe. The meaning of an index saprobe equal 3,53 shows, that waters of lake concern to polysaprobe to a zone. And the researches carried out in 2011-2012 years show,that the meaning the indicator - saprobe of kinds has increased up to 25 kinds and saprobe the index was equal 2,61,therefore that water of lake concerns to α-mezosaprob to a zone. During research it`s defined that the lost years because of reduction of some negative influences on water of the lake were characterized from polisaprobien zone into α-mesosaprobien.